Operational Cash Flow Analysis of PT Waskita Beton Precast Tbk Financial Performance 2014-2018 - Alfian Dwi Pambudi; Marliza Noor Hayatie; Muhammad Ghalih (International Journal of Research in Vocational Studies (IJRVOCAS), 2021)
This study aims to find the financial performance of PT Waskita Beton Precast Tbk during 2014-2018 in managing its operating cash flow. The analytical tool used in this study is ratio analysis. Types of ratio analysis used are operating cash flow ratios, the ratio of cash to interest coverage, ratio of cash to current debt ratio, ratio of capital expenditure, ratio of total debt, and the ratio of cash flow to net income. After calculating the cash flow ratio analysis, it can be concluded that for now, PT Waskita Beton Precast Tbk is still unable to be independent in capital expenditure. Despite that, PT Waskita Beton Precast Tbk has recorded a good improvement, therefore it can be estimated that in a few more years, the financial performance of PT Waskita Beton Precast Tbk will be very good.